The influence of river basin nitrogen pollution sources and their transport on microbial community structure - Sun, Qianhang; Li, Jiangnan; Zhou, Chunhe; Jiang, Weijun; Lei, Kun (Frontiers in Marine Science, 2024)
The characterization of variations in riverine microbiota that stem from contaminant sources and transport modes is important for understanding biogeochemical processes. However, the association between complex anthropogenic nitrogen pollution and bacteria has not been extensively investigated owing to the difficulties faced while determining the distribution of nitrogen contaminants in watersheds. Here, we employed the Nitrogen and Oxygen Stable Isotope Tools alongside microbiological analysis to explore microbial characteristics and their responses to complex nitrogen pollution patterns. Significant changes in microbial communities were observed in watersheds with different complex nitrogen pollution sources migrating. Complex nitrogen sources were closely associated with microbiota. The main sources of nitrogen pollution in the dry season watershed were Manurc and Sewage (M&S, 54.2%). M&S exhibited reduced microbial diversity, high number of denitrification groups, and increased nitrogen cycling compared with others. However, Soil Nitrogen sources (SN, 59.3%) in the watershed during the wet season were the main contributors of nitrogen in the watershed. Eluviation allows SN to increased microbial community similarity, in addition to facilitating microbial immobilization processes. Overall, this study expands our knowledge regarding microbial biogeochemistry in catchments and beyond by linking specific nitrogen pollution scenarios to microorganisms.